Cho x,y,z là các số thực khác -1. Chứng minh rằng:
A= $\frac{xy+2y+1}{xy+x+y+1}$ + $\frac{yz+2z+1}{yz+y+z+1}$ + $\frac{zx+2x+1}{zx+z+x+1}$ là một số nguyên
Cho x,y,z là các số thực khác -1. Chứng minh rằng:
A= $\frac{xy+2y+1}{xy+x+y+1}$ + $\frac{yz+2z+1}{yz+y+z+1}$ + $\frac{zx+2x+1}{zx+z+x+1}$ là một số nguyên
Giải thích các bước giải:
Ta có :
$\dfrac{xy+2y+1}{xy+x+y+1}=\dfrac{y(x+1)+y+1}{(x+1)(y+1)}=\dfrac{y}{y+1}+\dfrac{1}{x+1}$
Chứng minh tương tự ta có :
$\dfrac{yz+2z+1}{yz+y+z+1}=\dfrac{z}{z+1}+\dfrac{1}{y+1}$
$\dfrac{zx+2x+1}{zx+z+x+1}=\dfrac{x}{x+1}+\dfrac{1}{z+1}$
$\rightarrow A=\dfrac{y}{y+1}+\dfrac{1}{x+1}+\dfrac{z}{z+1}+\dfrac{1}{y+1}+\dfrac{x}{x+1}+\dfrac{1}{z+1}$
$\rightarrow A=\dfrac{y+1}{y+1}+\dfrac{x+1}{x+1}+\dfrac{z+1}{z+1}$
$\rightarrow A=3$